The Ideological Purpose and Content of the Work 'Raddu-l-mukhtar - Tursunov Muxiddin Dovudovich (Scientific Trends, 2025)
This study provides a comprehensive examination of the ideological purpose and content of Raddu-l-Mukhtar, one of the most influential works in Islamic jurisprudence authored by the renowned scholar Ibn ʿĀbidīn. The research highlights how the text transcends the boundaries of a mere legal commentary to become an ideological manifesto reflecting the theological, political, and social realities of its time. The work is analyzed as both a defense and consolidation of Sunni orthodoxy amid sectarian challenges, while also serving as a dynamic response to the intellectual and reformist movements of the 18th and 19th centuries within the Ottoman Empire. Through critical textual and contextual analysis, the study identifies the central ideological themes embedded in Raddu-l-Mukhtar, such as the preservation of Sunni authority, the reconciliation between tradition and modernity, and the critique of heterodox sects. Furthermore, the paper explores how Ibn ʿĀbidīn’s interpretative methods and scholarly reasoning illustrate a balance between adherence to classical Hanafi jurisprudence and responsiveness to evolving socio-political realities. The findings underscore the enduring relevance of Raddu-l-Mukhtar as a foundational text that not only codifies legal rulings but also shapes Muslim identity, intellectual discourse, and the ideological cohesion of Islamic legal thought. In conclusion, this study affirms the text’s role as both a legal and ideological cornerstone that continues to influence contemporary Islamic scholarship, demonstrating its capacity to bridge historical scholarship with modern interpretative needs.
Keywords: Raddu-l-Mukhtar, islamic jurisprudence, Sunni orthodoxy, ideological framework, tradition and modernity, Ibn ʿĀbidīn